The Effect of RAFT and Idea Filtering Strategies on Lateral Thinking among Second-Grade Intermediate Female Students in Biology (Journal of the College of Basic Education, 2025)
The current study aims to investigate the effect of the RAFT and Idea Filtering strategies on developing the lateral thinking skills of second-grade intermediate female students in the subject of Biology. To achieve this, the researcher formulated three null hypotheses concerning the absence of statistically significant differences between the mean scores of the experimental groups (RAFT and Idea Filtering) and the control group in the lateral thinking test, as well as no differences between the two experimental groups. The study employed a quasi-experimental design involving two experimental groups and one control group. A purposive sample of 102 female students from Al-Salihāt Intermediate School was selected, and equivalence among groups was established based on several variables including prior achievement, intelligence, prior knowledge, and lateral thinking test scores. The researcher developed 145 behavioral objectives according to Bloom’s taxonomy and submitted them to experts for validation. Additionally, 48 lesson plans were prepared and reviewed for the research groups. Two research instruments were developed; the lateral thinking test consisted of 25 short essay items, its face validity was confirmed, and reliability was measured using Cronbach’s alpha (0.923). The researcher applied both instruments to the sample after the intervention period, personally taught the groups, and analyzed the results using an independent samples t-test. The study’s conclusions and recommendations are presented in Chapter Four.